2017
DOI: 10.1016/j.chom.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The Human Microbiome and Obesity: Moving beyond Associations

Abstract: Mounting evidence indicates that the gut microbiome responds to diet, antibiotics, and other external stimuli with speed and high precision and in ways that impact a variety of metabolic conditions including obesity and non-alcoholic fatty liver disease. Despite a decade of research establishing a strong association between the gut microbiota and obesity in humans, a causal relationship and the underlying mechanism remain outstanding. Several technological and methodological limitations in obesity and microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
279
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(290 citation statements)
references
References 90 publications
6
279
0
5
Order By: Relevance
“…38,39 The presence of viable bacteria in non-IBD controls is not unexpected given the underlying pathology in these patients. In addition, other factors that have been associated with changes to the microbiome, such as diet, 40 smoking, 41 medications 42 and obesity, 43 could not be controlled for. 4 There are several limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 The presence of viable bacteria in non-IBD controls is not unexpected given the underlying pathology in these patients. In addition, other factors that have been associated with changes to the microbiome, such as diet, 40 smoking, 41 medications 42 and obesity, 43 could not be controlled for. 4 There are several limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, animal studies have shown that gut microbes can influence weight gain and adiposity by affecting host gene expression, metabolic pathways, and the gut-brain-axis. 117 Moreover, weight loss interventions have also been associated with distinct shifts in the gut microbiome. A variety of surgical weight loss intervention in humans and in animals have shown distinct and long lasting microbial profile differences.…”
Section: Clinical Implications Of Altered Human Microbiomementioning
confidence: 99%
“…Through the portal vein that connects the liver to the gastrointestinal tract, the liver is exposed to the influence of the gut microbiome. Perturbations of the gut microbiome, coupled with disturbances in gut barrier function, have been associated with common liver disorders, such as non-alcoholic fatty liver disease [138][139][140], non-alcoholic steatohepatitis [139,[141][142][143][144][145][146][147][148][149][150][151][152], alcoholic liver disease [139,140,142,145,147,148,150,151,[153][154][155][156][157][158][159][160][161][162][163][164], and liver cirrhosis [165][166][167][168][169][170]. Thus, the microbiome serves as a modulator of liver rhythmic functions.…”
Section: Liver Functionmentioning
confidence: 99%